2020
DOI: 10.1021/acs.chemmater.0c03066
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Laterally Confined Blue-Emitting 3.5 Monolayer CdSe Nanoplatelets

Abstract: The typical synthesis protocol for blue-emitting CdSe nanoplatelets (NPLs) yields particles with extended lateral dimensions and large surface areas, resulting in NPLs with poor photoluminescence quantum efficiency. We have developed a synthesis protocol that achieves an improved control over the lateral size, by exploiting a series of long-chained carboxylate precursors that vary from cadmium octanoate (C8) to cadmium stearate (C18). The length of this metallic precursor is key to tune the width and aspect ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 49 publications
2
77
1
Order By: Relevance
“…13,27 Also, recently Di Giacomo et al reported that blue-emitting NPLs with photoluminescence quantum efficiencies of ∼30% in the emission wavelength of 459−463 nm were synthesized using a modified synthesis protocol. 37 In comparison to previous work, we synthesized highly efficient with CdSe 1−x S x /CdS core/crown NPLs in the spectral range of ∼462−487 nm with PL-QY of ∼60%. These results are highly promising for light-emitting diode applications.…”
Section: Resultsmentioning
confidence: 99%
“…13,27 Also, recently Di Giacomo et al reported that blue-emitting NPLs with photoluminescence quantum efficiencies of ∼30% in the emission wavelength of 459−463 nm were synthesized using a modified synthesis protocol. 37 In comparison to previous work, we synthesized highly efficient with CdSe 1−x S x /CdS core/crown NPLs in the spectral range of ∼462−487 nm with PL-QY of ∼60%. These results are highly promising for light-emitting diode applications.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike thicker‐ML CdSe NPLs, which exhibit a moderate PLQY of around 30% and moderate colloidal stability, thinner 3‐ML NPLs grown under a much lower temperature (≈180 °C) demonstrate much lower PLQY (<10%) and a strong tendency of precipitation due to the large lateral surface and poor surface passivation. A recent published work [ 70 ] proposed a modified hot‐injection method by replacing long‐chain cadmium precursors with short‐chain cadmium carboxylates to synthesize 3‐ML CdSe NPLs with improved PLQY up to 30% and even thinner 2‐ML CdSe NPLs with the emission position blueshifted to 393 nm and PLQY up to 11%. Due to the successful realization of colloidal CdSe NPLs with tunable PL peak wavelength spanning from the blue to green spectral region, tremendous efforts have been made in the search for synthetic approaches to produce thicker CdSe NPLs with narrower bandgap.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
“…In summary, the previous literature reported that core/shell NPL–based LEDs exhibit the highest EQE comparable to state‐of‐the‐art QD LEDs as well as wide spectral tunability in the visible region. However, although lots of efforts have been made on the optimization of 3‐ML‐CdSe NPLs with blue emission, [ 70 ] no report on blue‐emitting CdSe NPL–based LEDs has been published due to poor surface passivation and low stability in these ultrathin NPLs. With the established synthesis of graded‐core/grade‐shell hetero‐NPLs, blue‐emitting NPL LEDs could be fabricated with the optimized design of the synthesis protocol and device structure in the future.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
“…This can be attributed to the large intrinsic absorption coefficient of 3 ML CdS/CdSe core/crown NPLs, which makes them excellent candidates as optical gain media as the intrinsic absorption shows the gain capability of a material. [ 13,40,41 ] The previously reported best gain coefficient in the blue region for solution‐processed materials is also from core 3 ML CdSe NPLs demonstrating the potential of these thin QRs of CdS/CdSe NPLs. [ 31 ]…”
Section: Resultsmentioning
confidence: 92%
“…
light-emitting diodes and lasing, [1] as a result of their unique optical and electronic properties such as giant oscillator strength, [2] exceptional color purity owing to their magic-size vertical thickness, [3] photoluminescence (PL) quantum yields reaching near-unity, [4][5][6] directed emission profile, [7][8][9] switchable excitonic polarization, [10] and spectral tunability as a result of their lateral size and thickness control at monolayer (ML) precision. [11][12][13] These quasi-2D structures further enable unique opportunities for the design of novel heterostructures as a result of the possibilities of isotropically growing a shell around the entire core seed with atomic layer precision [12,14,15] and/or anisotropically only a crown [16][17][18] with an identical number of monolayers fixes vertical thickness as the seed core, as an purely lateral extension (wings) which is otherwise not possible at such a level of selectivity for other types of solution-processed nanocrystals in different geometries, for example quantum dots (QDs). Using heterostructures of NPLs, amplified spontaneous emission (ASE) with ultralow thresholds, [19][20][21][22][23] large modal gain, [19,21] long gain lifetime, [21,24] and stable ASE [21,25] and lasing [26] have been recently reported in the green and red regions of the visible spectrum using 4 ML CdSe/CdS core/crown, CdSe/Cd 1-x Zn x S core/shell, and CdSe/CdS/Cd 1-x Zn x S core/crown/shell NPLs.
…”
mentioning
confidence: 99%